El sistema penitenciario y carcelario en Colombia: El concepto de alta seguridad en la justicia especializada - Baracaldo Méndez, María Stella (Revista policía y seguridad pública, 2014)
Colombia inherited a culture of political conflict from the civil wars of the nineteenth century. After a hiatus, it reappeared in the forties in the confrontation of the traditional parties (liberal and conservative), and beginning in the fifties, there emerged guerrilla groups, paramilitary forces, drug-trafficking rings, common and organized crime, to name a few. This gave way to a new and complex conflict. Since 1978, the the State of Internal Unrest has predominated. This has been the measure for managing internal security without recognizing the armed conflict. The 1991 constitutional reform introduced a new system of justice, which has generated an average 1,500 inmates on a monthly basis. At this rate, the prisons are currently beyond capacity. They are managed under the system of minimum, medium and maximum security. Presently, President Santos declared the existence of the conflict, and he has called for a transitional justice for the peace process. As a result, the Penitentiary and Prison Code is undergoing reforms, and a state of emergency was declared in the prisons as the level of overcrowding has reached 52%, and there are serious violations to the inmate population’s human rights.DOI: http://dx.doi.org/10.5377/rpsp.v3i1.1330Colombia heredó de las guerras civiles del siglo XIX una cultura de conflicto político, que tras un descanso, reapareció en la década de los cuarenta con la confrontación de los partidos tradicionales (liberal y conservador) y desde los años cincuenta con la aparición gradual de grupos de guerrilla, autodefensas, narcotraficantes, delincuencia común y organizada, entre otros, dando paso a un nuevo y complejo conflicto. Desde 1978 ha predominado la medida del Estado de Conmoción Interior para manejar la seguridad interna sin el reconocimiento del conflicto armado. La reforma constitucional de 1991 introdujo un nuevo sistema de justicia que, por mes, genera un promedio de 1500 reclusos, cantidad que actualmente desbordan la capacidad de las cárceles, administradas bajo el sistema progresivo de mínima, media y alta seguridad. Hoy, con la declaración del conflicto por el presidente Santos y una justicia transicional para el proceso de paz, está en curso la reforma del Código Penitenciario y Carcelario y fue decretada la emergencia carcelaria ante un nivel de hacinamiento del 52% y graves violaciones de derechos humanos de la población reclusa.DOI: http://dx.doi.org/10.5377/rpsp.v3i1.133